"We felt unsafe." Rethinking risk, harm, and safety in museums. (3rd July 2021) - Anderson, Suse
ABSTRACT: Museums are often imagined as "safe spaces for unsafe ideas, " yet such a conception ignores the real harms that museums can cause to individuals, communities, and publics. While, as a sector, we are skilled at calculating risks to the collection or institution, potential risks to publics, including staff, are rarely considered with the same rigor. It is still too rare that the question, "who might this harm?" is asked. However, the compounding crises of the COVID-19 pandemic, and the growing acknowledgment of systemic racism and oppression, create an opportunity for museums to change their practices related to risk and harm. This, therefore, becomes a critical moment to ask what it might mean to create institutions that feel safe and are safe, particularly for those have been - and continue to be - harmed. This short provocation will argue for a reframing of the relationship between risk, harm, and museums.